DYSPHAGIA AND SIALORRHEA: - NICARETTA,Denise Hack (2013)
ContextDysphagia and sialorrhea in patients with Parkinson's disease are both automatically accepted as dependent on this neurological disease.ObjectiveThe aim were to establish if these two complaints are a consequence or associated manifestations of Parkinson's disease.MethodTwo Parkinson's diseases groups from the same outpatients' population were studied. Patients in the first group, with dysphagia, were studied by videofluoroscopy. The second, with sialorrhea, were studied by the scintigraphic method,ResultsVideofluoroscopic examination of the oral, pharyngeal and esophageal phases of swallowing showed that 94% of Parkinson's diseases patients present, structural causes, not related to Parkinson's diseases, able to produce or intensify the observed disphagia. The scintigraphic examination of Parkinson's diseases patients with sialorrhea showed that there is no increase of serous saliva production. Nevertheless, showed a significantly higher velocity of saliva excretion in the Parkinson's diseases patients.ConclusionsDysphagia can be due to the muscular rigidity often present in the Parkinson's diseases patient, or more usually by non Parkinson's disease associated causes. In Parkinson's diseases patients, sialorrhea is produced by saliva retention. Nevertheless, sialorrhea can produce discomfort in swallowing, although without a formal complaint of dysphagia. In this case, subclinical dysphagia must be considered. Sialorrhea is indicative of dysphagia or at least of subclinical dysphagia. As final conclusion, Parkinson's diseases can be an isolated cause of dysphagia and/or sialorrhea, but frequently, a factor unrelated to Parkinson's diseases is the main cause of or at least aggravates the dysphagia.